Genomic Instability Promotes the Progression of Clear Cell Renal Cell Carcinoma Through Influencing the Immune Microenvironment - Wei, Xiyi; Wang, Yichun; Ji, Chengjian; Luan, Jiaocheng; Yao, Liangyu; Zhang, Xi; Wang, Shuai; Yao, Bing; Qin, Chao; Song, Ninghong (Frontiers in Genetics, 2021)
Background: The purpose of our study is to probe the role of genomic instability-derived lncRNA signatures and to further investigate the mechanism of genomic instability mediated ccRCC progression. Methods: The transcriptome data and somatic mutation profiles of ccRCC as well as clinical characteristics used in this study were obtained from TCGA database and GEO database. Lasso regression analysis was performed to construct genomic instability-derived lncRNA signature (GULncSig). GSEA was performed to elucidate the biological functions and relative pathways. CIBERSORT and EPIC algorithm were applied to calculate the proportion of immune cells in ccRCC. ESTIMATE algorithm was utilized to compute the immune microenvironment scores. Results: In total, 148 novel genomic instability-derived lncRNAs in ccRCC were identified. Immediately, on basis of univariate cox analysis and lasso analysis, a GULncSig wasappraised, through which patients were allocated into High-Risk and Low-Risk groups with significantly different characteristics and prognosis. In addition, we confirmed that the somatic mutation count, tumor mutation burden (TMB) and the expression of UBQLN4, which were ascertainably associated with genomic instability, were significantly correlated with the GULncSigs, indicating its reliability as a measurement of the genomic instability. Furthermore, the efficiency of GULncSig in prognostic aspects was better than single mutation gene in ccRCC. In addition, MNX1-AS1 was defined to be a potential bio-marker characterized by strong correlation with clinical features. Moreover, GSEA results indicated that IL6/JAK/STAT3/SIGNALING pathway could be considered as a potential mechanism of genomic instability to influence tumor progression. Besides, the immune microenvironment showed significant differences between GS-like group and GU-like group which was specifically manifested as high expression of CTLA4, GITR, TNFSF14 and Tregs as well as low expression of endothelial cells in GU-like group. Conclusion: In conclusion, this study provided a new perspective for the role of lncRNAs in genomic instability and reveled that genomic instability may mediate tumor progression by affecting immunity. Besides, MNX1-AS1 played critical roles in promoting the progression of ccRCC, which may be a potential therapeutic target. What’s more, the immune atlas of genomic instability was characterized by high expression of CTLA4, GITR, TNFSF14, T cells regulatory (Tregs) and low expression of endothelial cells.